كتاب العربية للحياة على نظرية علي القاسمي - Kamalludin, Kamalludin (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
In an Arabic language education institution, both formal and non-formal, it is mandatory to have books or modules available to serve as teaching and learning standards. This is based on the Minister of Education Regulation number 2 of 2008 Article 1 paragraph 3 which regulates the manufacture of textbooks and their objectives. Based on Ali Al-Qosimi's theory that in the preparation of Arabic books, there are three important things: 1) The main book as a teaching guide. 2) A companion book to the main book. 3) Recordings or sound media that are in harmony with the contents of the main book. The objectives of this study are: 1) To find out the contents of the book Al-'Arabiyah Lil Hayah Volume 1 in terms of the main material and accompanying material based on the theory of Ali Al-Qosimi. 2) To determine the suitability of the book with the theory of Ali Al-Qosimi. This research is a type of descriptive qualitative research using literature study as the method. Data collection techniques by means of documentation and analyzed by content analysis techniques. The results of this study are that the Book of ALH: 1) consists of the main material—the main book and companion material as well as media—dictionaries and websites. 2) The book is in accordance with Ali Al Qosimi's theory, in terms of the main material including material indicators, conversational texts, vocabulary, grammar and exercises, while the accompanying material and media are dictionaries and book websites.